Analisis Transaksi Jual Beli Ikan Terhadap Kesejahteraan Nelayan Dalam Perspetif Ekonomi Islam - Munawar, Ahmad Fauzi; Rahmani, Nur Ahmadi Bi; Nasution, Juliana (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the impact of fish trading transactions on the welfare of fishermen in Medan Deras Village and examine this situation from an Islamic economic perspective. The research method used is descriptive qualitative through in-depth interviews, observation, and documentation studies of fishermen as the main actors in the transactions. The results show that the fish trading mechanism is still dominated by distributors and traders, thus placing fishermen in a weak bargaining position. Unfair pricing practices and dysfunctional Fish Marketing Places (TPI) cause fishermen to receive incomes that are not commensurate with the efforts and risks incurred. From an Islamic economic perspective, this condition does not reflect the achievement of falah and maslahah, because there are still elements of zulm (injustice), economic coercion, and the unfulfilled principles of maqashid sharia, particularly the protection of property (hifz al-mal) and peace of mind (hifz al-nafs). This study emphasizes the need for reform of the marine product marketing system, strengthening sharia institutions, and fair pricing mechanisms to improve the welfare of fishermen holistically.